2013
DOI: 10.1007/s13311-013-0203-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Axon Outgrowth and Regeneration in CNS Injury: The First Steps Forward

Abstract: Inadequate axonal sprouting and lack of regeneration limit functional recovery following neurologic injury, such as stroke, brain, and traumatic spinal cord injury. Recently, the enhancement of the neuronal regenerative program has led to promising improvements in axonal sprouting and regeneration in animal models of axonal injury. However, precise knowledge of the essential molecular determinants of this regenerative program remains elusive, thus limiting the choice of fully effective therapeutic strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 133 publications
(142 reference statements)
0
28
0
Order By: Relevance
“…Epigenetic Mechanisms of Axon Regeneration-As epigenetic regulation of gene expression becomes more fully understood, the prospect that the epigenetic state of the neuron might significantly influence its intrinsic growth capacity becomes more compelling (168,169). In the last few years, experimental manipulation of chromatin dynamics in injury models has provided valuable insight into epigenetic influence on axon regeneration.…”
Section: Importance Of Proteomics In Identifying Mechanismsmentioning
confidence: 99%
“…Epigenetic Mechanisms of Axon Regeneration-As epigenetic regulation of gene expression becomes more fully understood, the prospect that the epigenetic state of the neuron might significantly influence its intrinsic growth capacity becomes more compelling (168,169). In the last few years, experimental manipulation of chromatin dynamics in injury models has provided valuable insight into epigenetic influence on axon regeneration.…”
Section: Importance Of Proteomics In Identifying Mechanismsmentioning
confidence: 99%
“…Acetylation of histone tails interdicts electrostatic interactions between histone proteins and DNA, and thus favors a more transcriptionally competent state [46,47]. As transcription appears to be required for neurite outgrowth, a reasonable model is that small molecules that bias histones toward an acetylated state [histone acetyltransferase activators (see article by Boutillier et al in this issue [48]) or HDAC inhibitors (see articles by Di Giovanni et al [49], Wagner et al [50], and Roskams et al [51] in this issue)] should enhance neurite outgrowth and stroke recovery. HDAC inhibitors are believed to bias gene expression toward the growth program via effects on nuclear and axonal HDACs.…”
Section: Hdac and Hats In Axonal Sprouting Post-strokementioning
confidence: 99%
“…DNA chromatin modifications alter gene expression, a process known as epigenetic regulation. Recent studies have demonstrated that epigenetic regulation could be closely related to development, plasticity of neurogenesis, and axonal outgrowth and regeneration (reviews by Lindner et al and Hirabayashi et al [33, 34]). Roughly speaking, epigenetic regulation can be categorized into DNA methylation and histone modification.…”
Section: Strategies To Promote Axonal Regeneration In Cnsmentioning
confidence: 99%